Status and outlook for reconciliation of situation in Afghanistan - A. Rasulov (Международная аналитика)
The article describes the possibilities of SCO expansion and its transformation from regional to global structure. The SCO development strategy and actual needs of organization are analyzed.The main attention is paid to Afghanistan and Iran. The ways of overcoming disproportions between political and economic activities within SCO are submitted for consideration.